PENDAMPINGAN RADIOGRAFER TENTANG PERAWATAN DAN PENGUJIAN LEAD APRON DI RUMAH SAKIT WILAYAH KOTA YOGYAKARTA - ayu wita sari; Efita Pratiwi Adi (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2021)
The problem with partners is that there has never been an inspection or special inspection on the lead apron. This mentoring activity consists of the PKM Team and several students who have been equipped with skills. The PKM team was divided into several working groups including, working group I prepared tools and materials, Working Group II prepared documentation and working group III conducted a lead apron leak test. Working Group IV conducts evaluation and outreach to be conveyed to all radiographers in each hospital regarding the proper and correct conditions and procedures for apron care. Assistance activities and during monitoring and evaluation the lead apron is in good condition for maintenance. Only 18.75% are still hanging because the storage area is not possible and the lead apron is not suitable for use. Likewise, there is a pressure above the lead apron of around 6% and this is a condition that is no longer suitable for use so it is not a problem. This activity concluded that: increased knowledge of radiographers about proper and correct lead apron care; increased radiograph skills after training and mentoring; improved quality of personal protective equipment from radiation after treatment.